PENGARUH PENERAPAN STRATEGI GENIUS LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 35 PADANG - Sartika, Maya; Rahmi, Rahmi; Suryani, Mulia (STKIP PGRI Sumbar, 2013)
This research is supported by conventional learning process, so that students learning styles are less accommodation. In fact, the students understanding of mathematical concept are very low. It seems from the results of grade nine at junior high school 35 Padang. The purpose of this research is to know students understanding of mathematical concept by applying Genius Learning Strategy is better than students understanding of mathematical concept by applying conventional learning. The kind of this research isnexperimental research by designing randomized research to subject. Form of test used is a form of essay with a reliability test is . The data analysis technique used is the one party t test with the help of MINITAB. Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples at and the results obtained from testing the hypothesis P-Value means less than , then the hypothesis in this study received. It can be concluded that the students understanding of mathematical concepts that apply Genius Learning strategies are better than student understanding of mathematical concepts by applying conventional learning grade nine junior high school 35 Padang .